The Effectiveness of Health Promotion Media on Increasing Knowledge and Participation of Women of Reproductive Age in VIA Screening: A Systematic Literature Review - Astin Nur Hanifah; Nana Usnawati; Nuryani Nuryani (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2026)
Introduction: Cervical cancer remains a major cause of morbidity and mortality among women in Indonesia, largely due to low awareness and limited participation in Visual Inspection with Acetic Acid (VIA) screening. Health promotion media are essential to improving knowledge, shaping positive attitudes, and increasing willingness to participate in early detection efforts. This systematic literature review evaluates the effectiveness of various health promotion media in increasing knowledge and VIA screening participation among women of reproductive age (WRA). Methods: This review followed the PRISMA 2020 protocol. Literature searches were conducted exclusively through Google Scholar for studies published between 2021 and 2025. Thirteen eligible studies were analyzed using the PICO framework, focusing on population characteristics, intervention types, comparison strategies, and measured outcomes. Most studies used quasi-experimental pre-post designs. This review has limitations, including reliance on a single database, restriction to Indonesian studies, and predominance of quasi-experimental designs without control groups. These limitations may introduce selection bias and reduce generalizability. Results: Overall findings show significant improvements (p<0.05) in knowledge, attitudes, and VIA participation following health promotion interventions. Audiovisual media, mobile-based applications and live demonstrations produced the strongest effects by enhancing multisensory learning and reducing psychological barriers such as fear or embarrassment. Printed media, including booklets, modules and leaflets remained effective as complementary tools, especially in areas with limited digital access. Intervention success was also supported by family involvement, cultural appropriateness, and active engagement of health workers. Conclusion: In conclusion, multimodal and community-centered health promotion strategies are effective in increasing WRA knowledge and participation in VIA screening. Future research should employ stronger methodological design, expand database coverage, and incorporate cross-national comparisons to enhance the evidence base for cervical cancer screening programs.